Constituyentes químicos de fracciones no polares y actividades biológicas de las hojas de Eugenia myrcianthes (Myrtaceae) - Letizia Grau; Luis Marin; Francisco Ferreira; Elvio Gayoso; Juliana Moura - Mendes; Daniela Gamenara (Lilloa)
The genus Eugenia (Myrtaceae) represents an important source of medicinal species, with documented biological activities attributed to its diverse secondary metabolites, particularly phenolic compounds and terpenoids. However, comprehensive toxicological evaluation remains essential to validate the safety of traditional applications. This research aimed to evaluate the chemical constituents of non-polar fractions and the bioactive potential of Eugenia myrcianthes (Yva hái) leaves. Analyses were performed on hexane, chloroform, and aqueous fractions obtained from the ethanolic extract of the plant material. Phytochemical screening revealed the presence of phenolic compounds, flavonoids, tannins, saponins, and triterpenes/steroids. Gas chromatography-mass spectrometry (GC-MS) identified major bioactive constituents as Delta-cadinene, Alfa-tocopherol, phytol, and squalene in the chloroform fraction, while Tau-muurolol, stigmasterol, Beta-amyrone, and lupenyl acetate were detected in the hexane phase. Bioactivity assessment demonstrated remarkable antioxidant capacity in the aqueous portion (DPPH IC50 = 18.5±0.33 ug.mL-1), contrasting with limited antimicrobial effects against Escherichia coli, Salmonella typhimurium, Staphylococcus epidermidis, and Staphylococcus aureus strains at ?2500 ug.mL-1. Furthermore, no toxicity was detected at ?20 mg.mL-1 using Drosophila melanogaster as a model organism. These findings highlight E. myrcianthes as a promising source of natural antioxidants. Further research into its specific bioactive compounds is necessary to fully assess the plant’s therapeutic potential.